SAKSI NON MUSLIM TERHADAP ASAL USUL ANAK PERSPEKTIF HUKUM ISLAM PADA PENETAPAN NOMOR 99/Pdt.P/2022/PA.Kdr: Konsep Saksi Dalam Hukum Positif dan Hukum Islam - Isfaul Isfaul Khasanah; Rayno Rayno Dwi Adityo (Syakhsia Jurnal Hukum Perdata Islam, 2023)
Abstract The process of proving in a religious court is a very crucial process. Due to the large number of people with various religions, it is not uncommon for non-muslim witnesses to be presented in the trial to be witnesses. Islamic law requires witnesses to be Muslim. This study aims to examine non-muslim witnesses in the determination of Number 99/Pdt.P/2022 / PA.Kdr on the origin of children perspective of Islamic law. This study is a normative legal research using case approach, statue approach and legal literature study. The method of data collection by using continuous literature studies with non-muslim witnesses and Islamic law with the limitation of the scope of the imams of the madhhab, namely imam Hanafi, Imam Malik, Imam Shafi'i and Imam Ahmad and contemporary scholars. The results of this study led to three conclusions. First, the testimony of non-Muslims is not accepted by the scholars of madhhab but there are also those who accept that the legal consequences remain valid in decision number 99/Pdt.P/2022 / PA.Kdr about the origin of the child, either because of emergency or on the social conditions of each. Secondly, the requirement of a Muslim witness in determining the status of the child's origin is not clearly regulated in positive law. Third, the testimony of non-Muslims in decision number 99 / Rev.P/2022 / PA.The Kdr on the origin of the child is still accepted by the judge based on the judge's ijtihad. Keywords: Verdict, Non Muslim Witnesses, Islamic Law.